Agrar- und Umweltpolitiken aus institutioneller Sicht: Eine ex-ante Methode zur Politikbewertung; Agricultural and Environmental Policies from an Institutional Economics Perspective: a Method for Ex-ante Policy Assessment - Christian Schleyer; Insa Theesfeld (German Journal of Agricultural Economics (GJAE), 2011)
– Ex-ante impact assessment of agricultural, environmental, and rural policies has become an integral part of political decision-making processes in the European Union. While a variety of agri-environmental modelling tools exists which are able to predict social, economic, and ecological consequences of policies, there are no standardised ex-ante policy assessment tools capturing the institutional dimension. In this paper, we introduce a procedure for ex-ante modelling institutional aspects for policy implementation. PICA (Procedure for Institutional Compatibility Assessment) is a systematic methodology to assess the institutional compatibility of policy options with the respective national and regional institutional contexts. PICA has been designed as an explorative, yet formalised methodology that enables policy-makers to identify, at an early stage, potential institutional incompatibilities. After a brief introduction of the concept of institutional compatibility for policy assessment, the four distinct steps of PICA are elaborated. Subsequently, the practical and empirical processes as well as the results of the application of PICA for the (in the year 2007) planned implementation of the EU-Nitrate Directive in the Deṕartement Puy-de-Dom̂e in the Auvergne, France, will be presented. In the conclusions we stress PICA's explorative character and give an outlook on the further methodological development of the procedure.
Keywords: 330; Agrarpolitik; Umweltpolitik; Institutionelle Infrastruktur; Wirkungsanalyse; Puy-de-Dome (Dep.); EU-Staaten